Glucose-Regulated HLP1 Acts as a Key Molecule in Governing Thermomemory. Issue 2 (19th March 2019) - Sharma, Mohan; Banday, Zeeshan Zahoor; Shukla, Brihaspati N.; Laxmi, Ashverya
Abstract : A glucose-TOR-E2Fa module regulates thermotolerance and thermomemory via regulation of HLP1. Abstract: Induction of heat shock proteins (HSPs) in response to heat stress (HS) is indispensable for conferring thermotolerance. Glc, a fundamental signaling and metabolic molecule, provides energy to stressed seedlings to combat stress. The recovery of stressed plants from detrimental HS in response to Glc is largely mediated by HSPs, but the mechanistic basis of this thermotolerance is not well defined. In this study, we show that Glc has a prominent role in providing thermotolerance. Glc-mediated thermotolerance involves HSP induction via the TARGET OF RAPAMYCIN (TOR)-E2Fa signaling module. Apart from HSPs, TOR-E2Fa also regulates the Arabidopsis ( Arabidopsis thaliana ) ortholog of human Hikeshi, named HIKESHI - LIKE PROTEIN1 ( HLP1 ). Expression of proHLP1 :: GUS in the shoot apical meristem (SAM) after HS coincides with TOR-E2Fa expression, substantiating a role for TOR-E2Fa-HLP1 in providing thermotolerance. We also demonstrate that Glc along with heat could induce proliferation activity in the SAM after HS recovery, which was arrested by the TOR inhibitor AZD-8055. Molecular and physiological studies suggest that HS-activated heat stress transcription factor A1s also positively regulate HLP1 transcription, suggesting convergence of the Glc and HS signaling pathways. Loss of functional HLP1 causes HS hypersensitivity, whereas HLP1 overexpressors display increased thermotolerance. HLP1 binds to the promoters of Glc-regulated HS-responsive genes and promotes chromatin acetylation. In addition, Glc modifies the chromatin landscape at thermomemory-related loci by promoting H3K4 trimethylation (H3K4me3). Glc-primed accumulation of H3K4me3 at thermomemory-associated loci is mediated through HLP1. These findings reveal the novel function of Glc-regulated HLP1 in mediating thermotolerance/thermomemory response.